A Feasibility Study on the Establishment of Delissio Vegezzain Bagumbong-Dulo, Caloocan City (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
Pizza became a blast in the food industry because it is an easy meal, and it has many flavors. The researchers came up with the idea of enhancing one of the flavors to make it more interesting and unique. That is the reason why the Delisio Vegezza was established. The unique part of the Delissio Vegezza is that the sauce and dough have vegetables. This study aims to help consumers have delicious and affordable food without risking their health. The researchers used the survey method in gathering data that will determine the level of satisfaction of the respondents. In this study, the researchers used questionnaires that were distributed to the chosen respondents. The researchers found out that the Delissio Vegezza was highly acceptable in the market with 100% respondents who like the taste of the pizza. On the other hand, 60% of the respondents want to have different toppings that are not on the menu. In terms of the suggested retail price, 80% of the respondents chose Php.40-Php.50. On the distribution of the pizza crust, 60% chose the pizza crust with stuffed cheese. For the side dishes, the majority of the respondents like to have side dishes. Also, the researchers found that a similar business already exists. According to Alvarez et.al (2017) in the study “A Feasibility Study on the Establishment of 'Pizzatified' a Pizza with the Filipino Style toppings in the Hub Food Park at Zabarte Road Quezon City”, there should be a continuous search for more flavours and focus on new trends like healthy options, environmentally conscious, fast restaurant, and technology enablement. Therefore, the proponents search for a particular product that can be innovated and competitive in the market.
Keywords: pizza, delissio vegezza, BCP